INTERFAITH DIALOGUE STRATEGIES FOR STRENGTHENING RELIGIOUS MODERATION (ISLAM WASATHIYAH) IN THE PUBLIC SPHERE - Zainol Hasan; Ali, Azimah Haji; Al-Rashid, Fatimah (World Psychology, 2025)
The rise of religious polarization threatens Indonesian pluralism, necessitating the state-endorsed paradigm of Islam Wasathiyah (Religious Moderation). However, the efficacy of traditional interfaith dialogue in translating this theological ideal into measurable public behavior remains empirically unverified. This study aimed to empirically evaluate the differential impact of two primary dialogue strategies—Theological Exchange (Strategy A) and Joint Social Action (Strategy B)—on strengthening key dimensions of moderation (Tolerance, Empathy, Anti-Extremism) among key public sphere demographics. A quantitative, quasi-experimental pre-test/post-test control group design was employed (N=294), recruiting university students and community leaders. Data were analyzed using MANCOVA to control for baseline scores across the three experimental groups over a six-week intervention period. Both active strategies significantly improved moderation compared to the control group (Wilk’s Λ = 0.655, p < .001). However, Strategy B (Joint Social Action) proved statistically superior to Strategy A, producing significantly greater gains in Tolerance and Perceived Empathy (both p < .001). Qualitative data confirmed that building a shared civic identity through collaborative work mediated this superior affective change. The findings mandate a strategic shift: the most potent public sphere strategy for strengthening Islam Wasathiyah is rooted in the experiential efficacy of shared, non-religious work, not purely intellectual debate. This conceptual model provides an evidence-based mechanism for translating the theological ideal into robust, affective cohesion.